Addition of Mitoquinone (MitoQ) to Fresh Human Sperm Enhances Sperm Motility without Attenuating Viability - Nehad Al-Tarayra; Zina M. Al-Alami; Abdelkader Battah; Nadia Muhaidat (Biology)
The preparation of human sperm in an andrology laboratory subjects it to oxidative stress. Reactive oxygen species are produced by mitochondria, making it susceptible to oxidative damage; hence, mitochondria-targeted antioxidants like Mitoquinone (MitoQ) might have therapeutic potential for oxidative-damage-associated disorders. The current research aims to establish whether MitoQ has any positive effects during in vitro preparation of fresh human sperm. Viability and motility are evaluated to determine the effective MitoQ concentration and to assess whether MitoQ supplementation is affected by sperm concentration by incubating normospermia semen samples at 37 °C for 2 h and 4 h, respectively. The effect of semen centrifugation following supplementation of 20 × 106 sperm/mL with 200 nM MitoQ is also assessed by measuring viability, motility and sperm DNA fragmentation. The best sperm motility is achieved after 2 h of incubation with 200 nM MitoQ at 37 °C. Sperm concentration of 20 × 106 sperm/mL is the best concentration where 200 nM MitoQ works efficiently. For semen centrifugation at 300× g for 20 min, supplementation with 200 nM MitoQ shows higher sperm motility. The current results demonstrate that MitoQ supplementation during in vitro human semen preparation procedures positively affects fresh sperm motility without affecting viability or increasing DNA fragmentation.